Hungarian émigrés in the American Civil War : a history and biographical dictionary - Vida, István Kornél, 1977- (McFarland, 2012)
"This thorough analysis of the Kossuth émigrés fighters explores their motivations and the military role they played during the American Civil War, often challenging the traditional hero-making mechanisms of ethnic history-writing in the process. The included biographical list of all Hungarian-born Civil War participants fills a longstanding gap in Civil War genealogy."--Provided by publisher